Research on Optimization of Training Path for Intelligent Financial Talents in Digital Economy Era - Zhang, Yijun; Yuan, Dan (Journal of Educational Research and Policies, 2025)
At present, as an important support for cultivating and expanding new quality productivity, the rapid development of digital economy has caused changes in employment structure and employment quality, and the transformation of financial talents is imminent. This paper expounds the impact of digital economy on the accounting industry, points out the existing problems in the training of financial talents in colleges and universities, and believes that colleges and universities can optimize the training path of intelligent financial talents from the aspects of changing the orientation of talent training, adjusting the course structure system, emphasizing the training of “finance + technology” composite ability and strengthening the construction of teachers.